Innovation and Agility in the Digital Age - Frimousse, Soufyane (Wiley-ISTE, 2019)
Africa is a laboratory for managerial and societal innovations built out of pragmatic arrangements. Some African companies offer products and services that go beyond the standard practices of their international counterparts, based on original and inventive managerial characteristics. Such success stories outline a new model of management and innovation for companies in the digital era. The African innovations that have emerged over the past ten years are directly linked to a managerial model that perfectly meets the demands of the digital era. These new organizations indicate that good managerial practices and innovation models also come from the Global South and no longer exclusively from the East Coast of the United States. Understanding these dynamics is of great theoretical and practical interest for the many companies struggling to seize the opportunities for growth in Africa.